Green kopitiams: Operators’ awareness and readiness - Juliana Langgat; Noor Fzlinda Fabeil; Khairul Hanim Pazim; Marry Tracy Pawan (Universal Publishers, 2022)
Operator awareness and readiness are critical to ensure the sustainability of the ecosystem, so this study investigates the awareness and readiness of kopitiam operators to implement green practices in their operations. A quantitative approach was utilised for this study. In total, 149 kopitiam operators in Kota Kinabalu city has participated in this study via a selfadministered survey. The items were measured using a five-point Likert scale (1 = strongly disagree to 5 = strongly agree). The gathered data were analysed using cross-tabulation analysis to investigate the kopitiam operators’ awareness of, and readiness to, implement green practices. This study identified two significant findings relating to the awareness and readiness of kopitiam operators ¬¬to implement green practices at their coffee shops. First, the kopitiam operators are aware of the importance of green practices, eco-friendly cleaning supplies and packaging, and menu sustainability. Surprisingly, installing energy- and water-efficient equipment in their premises seems not to be the main priority when implementing green practices, since high operational costs would be involved. The second finding concerns the readiness to participate in green practices. The kopitiam operators’ awareness was measured by assessing the importance of green practices, the installation of energy- and water-efficient equipment, the use of eco-friendly cleaning supplies and packaging, as well as offering a sustainable menu. The kopitiam operators’ readiness was measured through their participation in green practices. Further studies should investigate the awareness and readiness of kopitiam operators located in the other main cities of Sabah. The city council and restaurant association can use these findings to promote green practices to the other business operators involved in the food and beverages sector. Kota Kinabalu City Council (DBKK) could develop proper guidelines and procedures to implement these practices to achieve the intention of promoting the city as a green city. Kopitiams play an essential role in providing food and drinks for tourists who want to experience the local destinations. Therefore, this study could derive a more holistic strategy that promotes Sabah as a major eco-tourism destination in Malaysia.